ANALISIS NILAI TAMBAH DIVERSIFIKASI PRODUK OLAHAN KACANG TANAH DI KELURAHAN SIKUMANA, KECAMATAN MAULAFA, KOTA KUPANG - Tulle, Nikita Priscilla; Olviana, Tomycho; Elvani, Siska (Undana Press, 2024)
This study was conducted with the aim of knowing the description of the production process of peanut processing into egg peanuts and onion peanuts, and to determine the added value and profits generated by the processing of peanuts into egg peanuts and onion peanuts, as well as to find out the obstacles and solutions faced by IRT Sima Indah. The research was conducted at the office and location of IRT Sima Indah located together on Jl. Air Lobang 3 RT.37/RW.15 Sikumana Village, Maulafa District, Kupang City. This type of research is quantitative research using the method of interviewing business owners and workers and making direct observations. The sampling technique uses the census method, namely the population in this study is the business owner of the Sima Indah Home Industry, namely 5 workers. The results of this study indicate that the total costs incurred in the production process of egg beans and onion beans at IRT Sima Indah amounted to Rp. 19,985,423, total revenue of Rp. 25,020,000, then IRT Sima Indah got a profit of Rp. 12,631,494. The result of the added value given from the output value of every Rp.100 for each processed peanut product is Rp. 59 for egg peanut products and Rp. 50 for onion peanut products.